LITERASI PROGRAM PENGENDALIAN OBESITAS ANAK SEKOLAH DASAR DI JAKARTA SELATAN - Iskari Ngadiarti; Trina Astuti; Nur'aini Susilo Rochani; Marudut Sitompul; Arif Jauhari (Universitas Negeri Medan, 2021)
Abstract Overweight and obesity in school-age children have become public health problems. 75% of children who are obese at school age will be obese in adulthood. The first aim to monitor nutritional status, mentoring eating behavior, and physical activity for SDN students who have overweight and obese. The second goal is to increase the capacity of food keepers about good, healthy and safe food so that it can maintain the health of school children and control obesity. This community service was carried out at SDN Menteng Dalam 07 Pagi, targeting elementary school students in grades 4, 5, 6 who have over nutritional status and obesity and previously participated in the healthy class program held by the South Jakarta Health Office and local Puskesmas and canteen peddlers. Assistance was carried out for 1 month with monitoring of body weight, height, intake, and physical activity. After mentoring, it was found that the prevalence of nutrition decreased by more than 1.2%, decreased energy intake (8.9%), fat (2.2%), carbohydrates (8.9%), and increased physical activity by 11.1% in the category moderate. Beside that there was an increase in knowledge about healthy food and large portion of children’s meals according to their needs, and how to maintain good sanitation hygiene so as to maintain clean and safe food. The school’s commitment as a pilot school to control obesity was approved by policy makers and curriculum reforms will be carried out, especially to review physical activity curricula in schools. Keywords: School aged obesity, intake, physical activity, coaching